Can inaction account for the incomplete exchange rate pass-through? Evidence from threshold ARDL model. Issue 2 (3rd July 2019) - Konopczak, Karolina
ABSTRACT: Numerous empirical studies suggest that the responses of prices to exchange rate movements are muted, i.e. the exchange rate pass-through is incomplete. In this study we investigate whether this result can be explained by inaction to small changes in the exchange rate, in which case the incompleteness would constitute merely an artefact introduced by the linear specification of the pass-through equation. The results obtained for Polish industry show significant sign- and size-dependence in the sensitivity of export prices to exchange rate movements, but only in a few cases they fully account for the incompleteness of the pass-through. The tendency for inaction is to a large extent determined by industry's characteristics, with sectors more technologically advanced and more involved in international activities, more willing or able to absorb exchange rate movements in their markups, thereby stabilizing their prices in the destination markets.